On the optimum processing conditions of Pb(ZrxT1-x)O-3: revealing the mechanisms to increase the piezoelectric coefficients up to 1100 pm V-1 - Zeibekis, M.; Vertsioti, G.; Stamopoulos, D. (JOURNAL OF PHYSICS D-APPLIED PHYSICS, 2016)
The ferroelectric compound family Pb(ZrxTi1-x,)O-3 (PZT) is one of the most investigated and widely used piezoelectric materials. Optimization of the piezoelectric coefficients is observed for x similar to 0.52 (Pb(Zr0.52Ti0.48)O-3) and is further promoted by the increase of grain size (OS). However, in some cases the piezoelectric properties of Pb(Zr0.52Ti0.48)O-3 deteriorate upon processing due to the decrease of density, p, that is mostly ascribed to the appearance of byproduct phases. In the present study we discuss the influence of the processing conditions on the piezoelectric properties for polycrystalline Pb(Zr0.52Ti0.48)O-3, specifically focusing on the sintering temperature, 1100 degrees C Tsin <= 1250 degrees C. To this end, we use atomic force microscopy (AFM), Archimedes' method, x-ray diffraction (XRD) and a newly introduced local technique, based on a conventional optical microscope, which is further developed here to accommodate non-clamped specimens. The data obtained via this technique in the regime of relatively high electric fields evidence that the absolute piezoelectric coefficients, 141(i = x, y) show a non -monotonic behavior with an unexpectedly high maximum value broken vertical bar d broken vertical bar similar to 1100 pm V 1 at 7 = 1180 degrees C. These features are accompanied by a progressive increase of coercivity, reaching maximum value Ecj 4.5-5.0 kV cm I (i = x, y) at Tsin = 1250 degrees C. 'lb explain these findings, the Idzil coefficients are compared with the microstructure and compositional information, coming from AFM, Archimedes' method and XRD data. We conclude that the significantly high 141 values observed for samples prepared at Tsin = 1180 degrees C are motivated by the increase of mean GS, < GS >, while for Tsin > 1180 degrees C the decrease of density, p, ascribed to the appearance of byproduct phases, dominates and deteriorates Id2 I. These experimental results on broken vertical bar d broken vertical bar(T-sin) are reliably reproduced by a phenomenological model with reasonable assumptions for < GS > (7) 1 and rho(T(si)n). The unexpectedly high piezoelectric coefficients, broken vertical bar d(zi)broken vertical bar similar to 1100 pm V-1, reported here for the first time, are provocative and call for utilization of the introduced approach in the investigation of the respective properties of other compounds.